2021
DOI: 10.3390/ijerph18136772
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Benefits Matter the Most in COVID-19 Preventive Behaviors: Empirical Evidence from Okara District, Pakistan

Abstract: The 2019 coronavirus disease (COVID-19), caused by the SARS-CoV-2 virus has affected the social determinants of health, worsening health inequities and deteriorating healthcare capacities around the globe. The objective of this study is to investigate the COVID-19 prevention behaviors within the framework of the Health Belief Model in the city of Depalpur in the Okara District of Pakistan in May 2020. Using an observational, cross-sectional, and quantitative study design, a face-to-face field survey was conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
13
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 24 publications
(31 reference statements)
7
13
0
1
Order By: Relevance
“…Our study found a strong negative association between perceived benefits and the COVID-19 vaccine hesitancy. Considering a particular action (in this case, receiving vaccination) as effective in preventing a disease, which is perceived benefits according to HBM constructs, motivates individuals in adopting the behaviors [ 54 ]. On the other hand, perceived barriers were positively associated with vaccine hesitancy in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Our study found a strong negative association between perceived benefits and the COVID-19 vaccine hesitancy. Considering a particular action (in this case, receiving vaccination) as effective in preventing a disease, which is perceived benefits according to HBM constructs, motivates individuals in adopting the behaviors [ 54 ]. On the other hand, perceived barriers were positively associated with vaccine hesitancy in our study.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, a meta-analysis of HBM studies indicated that perceived benefit was the most powerful predictor among all the health belief factors [ 30 ]. Moreover, a study in the early stage of the COVID-19 pandemic revealed that the perceived benefits of preventative actions were positively associated with individuals’ intentions to take these actions [ 31 ]. Hence, we postulate the following hypothesis:…”
Section: Theoretical Model and Development Of Hypothesesmentioning
confidence: 99%
“…However, in another study conducted on the intentions for the uptake of H1N1 influenza vaccine, no evidence was found for a significant relation for P-SUS and P-SEV, whereas P-BEN and P-BAR were significant predictors of vaccine uptake [23]. Likewise, in a study conducted in Pakistan, Shah and colleagues (2021) [30] evaluated the role of HBM constructs in the adherence of preventive measure of COVID-19 and found the significant role of P-BEN, while the role of all other constructs in the adoption of preventive behavior, including cues-to-action, remained insignificant.…”
Section: Discussionmentioning
confidence: 95%